INVITATION TO THE DANCE: INTERMEDIAL ALLUSIONS IN T. S. ELIOT’S EARLY POETRY (“THE DEATH OF SAINT NARCISSUS”, “SUPPRESSED COMPLEX”) (Филологический класс, 2019)
The paper “Invitation to the Dance: Intermedial Allusions in T. S. Eliot’s Early Poetry (‘The Death of Saint Narcissus’, ‘Suppressed Complex’)” deals with some aspects of the early works by T. S. Eliot. The author examines relationships between dance, visual art and experiments in modernist poetry. The poems “The Death of Saint Narcissus” and “Suppressed Complex” are interpreted as the samples of a “dance-poem”. The poetic text incorporates the visual and plastic arts not only in a thematic way but poetic structure itself tends to the specific intermedial metamorphosis. The paper discusses the Ballet Russes Parisian productions of “Narcisse”, “Le Spectre de la Rose” and the performance of a mystery play “Le Martyre de Saint Sebastien” (1911) as the important sources for creation of the innovative poetic texts. The author also turns to some artifacts as the visual sources of intermedial allusions (the costume sketches and drawings by Leon Bakst, paintings by Henri Matisse’s, etc.). The main research argument is founded on the concepts of intermediality and intermedial allusions as important issues of modernist studies. The paper aims to prove the intermedial nature of Eliot’s poetic allusions, to examine in what way the visual arts and ballet influenced his texts and reveal the dynamic interactions between different kinds of art in the diachronic and synchronous perspectives. The paper presents a study of history of the creative process, cultural-historical and biographical contexts, peculiarities of the composition, the key images and themes, etc. The paper demonstrates in what way the intertextual, intermedial and other accompanying elements force the reader to reframe the original material and be included into the process of co-creation and formation a new intermedial narration. The results of this study could be helpful in teaching and research of history of English poetry, history and theory of modernism, in comparative studies (intermediality, reception of Russian culture abroad. etc.).